Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1038/s41467-022-34802-8
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic bacteria-dependent expansion of MR1-reactive T cells causes autoimmunity in the absence of Bcl11b

Abstract: MHC class I-related protein 1 (MR1) is a metabolite-presenting molecule that restricts MR1-reactive T cells including mucosal-associated invariant T (MAIT) cells. In contrast to MAIT cells, the function of other MR1-restricted T cell subsets is largely unknown. Here, we report that mice in which a T cell-specific transcription factor, B-cell lymphoma/leukemia 11B (Bcl11b), was ablated in immature thymocytes (Bcl11b∆iThy mice) develop chronic inflammation. Bcl11b∆iThy mice lack conventional T cells and MAIT cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Another population is TRAJ33 + T cells, which are rearranged with the non- TRAV1-2 segment and recognize unknown metabolites presented by MR1 [ 8 ]. We previously used a mouse model that shares clinical symptoms with AIP and revealed that the MR1-restricted Trav1 − Traj33 + non-MAIT cell population is associated with disease symptoms [ 5 ]. MAIT cells, defined by canonical TRAV1-2-TRAJ33 (human counterpart of mouse Trav1–Traj33 gene segment) expression, were present ( Figure 1E , black dots in upper plots) within a CD161 high αβ T-cell cluster in healthy donors ( Figure 1A , red dots), while such a cluster was unclear in patients with AIP ( Figure 1E , black dots in lower plots).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another population is TRAJ33 + T cells, which are rearranged with the non- TRAV1-2 segment and recognize unknown metabolites presented by MR1 [ 8 ]. We previously used a mouse model that shares clinical symptoms with AIP and revealed that the MR1-restricted Trav1 − Traj33 + non-MAIT cell population is associated with disease symptoms [ 5 ]. MAIT cells, defined by canonical TRAV1-2-TRAJ33 (human counterpart of mouse Trav1–Traj33 gene segment) expression, were present ( Figure 1E , black dots in upper plots) within a CD161 high αβ T-cell cluster in healthy donors ( Figure 1A , red dots), while such a cluster was unclear in patients with AIP ( Figure 1E , black dots in lower plots).…”
Section: Resultsmentioning
confidence: 99%
“…Another study showed CD4 + SLAM7 + T cells with cytotoxic activity that clonally expanded and were associated with clinical IgG4-RD symptoms [ 4 ]. It has been reported that, in a recently developed mouse model with a similar disease entity of AIP, clonally expanded T cell receptor alpha joining ( Traj ) 33 + T cells with a type 2 helper T (T H 2)-like phenotype contributed to autoantibody productions [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of autoimmune uveitis, recent findings on the therapeutic potential of TCR-mediated MAIT cell activation have motivated us to identify putative MAIT cell antigens in EAU mice. More detailed analysis of metabolites using highly sensitive mass spectrometry ( 70 72 ) and single metabolite-probing technology ( 73 ) will allow us to test this possibility.…”
Section: Discussion For Future Directionmentioning
confidence: 99%
“…Additionally, cancer cells have been shown to be targeted by MAIT cells utilizing an MR1-dependent mechanism, although with an unidentified ligand (29). Some atypical MR1related T cells (MR1T cells) are reported to respond to self-derived antigen(s) (30,31). Recently, Chancellor et al discovered the rare occurrence of self-reactive MAIT cells that display unique T-helper functions (32).…”
Section: Self Recognition By Mait Cellsmentioning
confidence: 99%